Strategi K-Radio Jember dalam Upaya Pemanfaatan Media Sosial sebagai Upaya Mempertahankan Audience di Era Digital - Rohim, Amatullah Azka Faadiya Haya Nurilalamin (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
In the midst of many radio stations losing listeners due to switching to digital media, K Radio Jember is here which can stand up to adapt to the era. By combining mass media with digital media, K Radio Jember is growing rapidly, and is even able to increase its audience. Through his social media accounts, it is proven that his followers and audience con-tinue to increase. So this is an interesting thing to research.The objec-tives of this thesis research are: 1) To determine K Radio Jember's strat-egy in utilizing social media as an effort to maintain its audience in the digital era. 2) To find out how K Radio Jemberis converging in facing the digital era.This research uses a qualitative approach method with a de-scriptive type. This research used observation, interviews and documen-tation to collect data. Data analysis techniques use data condensation, data presentation and data verification or conclusions. And for data va-lidity techniques in this research, triangulation analysis of data sources and techniques is used.This research concluded that: 1) K Radio's strat-egy in using social media as an effort to maintain its audience in the Dig-ital Era is the Compatibility Strategy, K Radio adapts to market seg-ments. Habit Formation Strategy, K Radio has a variety of regular week-ly program schedules. Control of Audience Flow Strategy. K Radio carries out monthly evaluationsand creates interesting content. Mass Appeal Strategy. K Radio has forayed into digital media through live streaming, and K Radio has become a space for aspirations and a way of connecting with the community. 2) The influence of K Radio in the use of social me-dia to maintain the audience, namely the audience is increasing and trusting K Radio, income, and becoming a forum for community aspirations and liaison.